2014
DOI: 10.1210/me.2014-1094
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BMP2-Induced Bone Formation by the p65 Subunit of NF-κB via an Interaction With Smad4

Abstract: Bone morphogenic proteins (BMPs) stimulate bone formation in vivo and osteoblast differentiation in vitro via a Smad signaling pathway. Recent findings revealed that the activation of nuclear factor-κB (NF-κB) inhibits BMP-induced osteoblast differentiation. Here, we show that NF-κB inhibits BMP signaling by directly targeting the Smad pathway. A selective inhibitor of the classic NF-κB pathway, BAY11-770682, enhanced BMP2-induced ectopic bone formation in vivo. In mouse embryonic fibroblasts (MEFs) prepared f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…We suggest that Ifrd1 deficiency inhibits the NF‐κB‐dependent transcription of Smad7 and subsequent activation of Smad1/Smad5/Smad8 signaling, leading to the promotion of osteoblastogenesis via Osx in osteoblasts. It has been demonstrated that the inhibition of NF‐κB promotes bone formation through the upregulation of JNK/Fra‐1, whereas p65 interacts with the Smad complex, subsequently disrupting its binding to target promoters and leading to the inhibition of Smad‐dependent transcription . We cannot exclude the possibility that Ifrd1–NF‐κB signaling regulates osteoblastogenesis through the JNK/Fra‐1 pathway or via direct regulation of the Smad pathway.…”
Section: Discussionmentioning
confidence: 93%
“…We suggest that Ifrd1 deficiency inhibits the NF‐κB‐dependent transcription of Smad7 and subsequent activation of Smad1/Smad5/Smad8 signaling, leading to the promotion of osteoblastogenesis via Osx in osteoblasts. It has been demonstrated that the inhibition of NF‐κB promotes bone formation through the upregulation of JNK/Fra‐1, whereas p65 interacts with the Smad complex, subsequently disrupting its binding to target promoters and leading to the inhibition of Smad‐dependent transcription . We cannot exclude the possibility that Ifrd1–NF‐κB signaling regulates osteoblastogenesis through the JNK/Fra‐1 pathway or via direct regulation of the Smad pathway.…”
Section: Discussionmentioning
confidence: 93%
“…Among the top 15 enriched TFs, there were a few which had previously been linked to BMP target gene regulation. For example, XBP1 and RELA have been shown to be repressors of BMP target genes Xvent-2 and Id1 , respectively [27, 28]. Using enrichment of the TFBSs between cell lines as well as other criteria, we selected three TFs (CBFB, HIF1A, and MBD2) for functional characterization and silenced them in the two cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts are not only responsible for bone formation but are also capable of supporting osteoclast development by producing RANKL. 1,25-Dihydroxyvitamin D 3 (1,25[OH] 2 D 3 ) is a well-known factor that induces RANKL and suppresses OPG, a decoy receptor for RANKL. (1) Therefore, we determined whether Mst2 is associated with osteoblast-regulated osteoclast development by evaluating the expression of Tnfsf11 and Tnfrsf11b, which encode RANKL and OPG, respectively, in the presence of 1,25 (OH) 2 D 3 .…”
Section: Mst2 Is Not Involved In Osteoblast-mediated Osteoclastogenesismentioning
confidence: 99%